Proyecto de Aplicación Digital Móvil: Let’s Train - Angulo Huamán, Ulises Jesús (2019)
This work will explain in detail the development and implementation of a startup with high growth and scalability potential, taking advantage of the support of technology and the trends that govern in today’s world. Our team developed the startup mentioned under the legal principles and moral requirements of the Peruvian University of Applied Sciences. Our team chose to develop a mobile application which its main function is to connect qualified coaches and athletes with final users, thus providing them with personalized or group training sessions. This application has been developed with the aim of helping people who love to learn and practice sports but who, nevertheless, do not have the time to travel to a training center or the schedules of these establishments do not fit into their day-to-day life. . Throughout this document, validations of the business model will be developed to verify its acceptance in the market, through experiments carried out as indicated in what was studied along this course.